Information diffusion and social norms are associated with infant and young child feeding practices in Bangladesh - Nguyen, Phuong Hong; Frongillo, Edward A.; Kim, Sunny S.; Zongrone, Amanda; Jilani, Amir Hamza; Tran, Lan Mai; Sanghvi, Tina; Menon, Purnima (Oxford University Press, 2019)
Interaction within mothers’ social networks can theoretically diffuse messages from interventions and campaigns into norms and practices for infant and young child feeding (IYCF).